Sonodynamic Therapy With Anticancer Micelles and High-Intensity Focused Ultrasound in Treatment of Canine Cancer - Horise, Yuki; Maeda, Masanori; Konishi, Yoshiyuki; Okamoto, Jun; Ikuta, Soko; Okamoto, Yoshiharu; Ishii, Hiroshi; Yoshizawa, Shin; Umemura, Shinichiro; Ueyama, Tsuyoshi; Tamano, Satoshi; Sofuni, Atsushi; et al. (Frontiers in Pharmacology, 2019)
Sonodynamic therapy (SDT) is a minimally invasive anticancer therapy involving a chemical sonosensitizer and high-intensity focused ultrasound (HIFU). SDT enables the reduction of drug dose and HIFU irradiation power compared to those of conventional monotherapies. In our previous study, mouse models of colon and pancreatic cancer were used to confirm the effectiveness of SDT vs. drug-only or HIFU-only therapy. To validate its usefulness, we performed a clinical trial of SDT using an anticancer micelle (NC-6300) and our HIFU system in four pet dogs with spontaneous tumors, including chondrosarcoma, osteosarcoma, hepatocellular cancer, and prostate cancer. The fact that no adverse events were observed, suggests the usefulness of SDT.